Efficiency of Sawdust as an Alternative Fuel to Replace Coal in Steam Power Plants - Muhammad Facheruddin BJ; A. Besse Riyani Indah; Gerard Antonini Duma (Protek: Jurnal Ilmiah Teknik Elektro)
This study aims to test the effectiveness of sawdust as an alternative fuel to replace coal in a 50 MW power plant in an effort to reduce dependence on fossil fuels and have a negative impact on the environment. The use of coal in power plants produces high carbon emissions that contribute to climate change. Sawdust, as a by-product of the wood industry, is considered an environmentally friendly fuel because of its abundant availability and its calorific value close to coal. This study was conducted by measuring the calorific value, fuel consumption, and electrical energy output produced during power generation using sawdust compared to coal. The measurement results show that the calorific value of sawdust is 3900 kcal/kg, slightly higher than coal, which has 3878 kcal/kg. Although the fuel consumption of sawdust is almost equivalent to coal, the energy output produced by sawdust (47,090 kWh) is lower than coal (50,900 kWh). The thermal efficiency of sawdust is recorded at around 25.72%, slightly lower than coal, which has an efficiency of 27.76%. Despite its lower efficiency, these results suggest that sawdust can still be a viable alternative fuel, especially if emission reduction and desirability are priorities. This study shows that sawdust has the potential to be a more environmentally friendly energy source and support efforts to transition energy towards a more sustainable system.